Reproductive characteristics of two Triturus species (Amphibia: Caudata) - Vučić, Tijana; Ivanović, Ana; Nikolić, Sonja; Jovanović, Jovana; Cvijanović, Milena (Archives of Biological Sciences, 2020)
Paper description: Two newt species, Triturus ivanbureschi and T. macedonicus hybridizе and form a moving hybrid zone in the central part of Serbia. In a common garden experiment, we collected data on the number and size of the deposited eggs, and the dynamics and duration of the oviposition period during three consecutive years. T. macedonicus females started oviposition later and laid more larger eggs in comparison to T. ivanbureschi. The obtained data and observed differences provide basic information on the biology of these two species. Abstract: During three consecutive years, we compared the reproductive characteristics and oviposition dynamics of two crested newt species, Triturus ivanbureschi and T. macedonicus. These two well-defined species are of special interest because of complex interactions at their contact zone, which include hybridization, species replacement and asymmetric mitochondrial DNA introgression. In common garden experiments, females were introduced to conspecific males, to males of other species and to hybrid males. We monitored the total number and size of the deposited eggs, as well as the dynamics and duration of oviposition during three consecutive years. The number of deposited eggs of Triturus species was much higher than previously reported. Triturus macedonicus lay more eggs that were of larger size in comparison to T. ivanbureschi. Also, the onset of T. macedonicus oviposition was considerably delayed compared to T. ivanbureschi. These are fundamental data, important for understanding complex species interactions in their contact zones. https://doi.org/10.2298/ABS200328026V Received: March 28, 2020; Revised: June 10, 2020; Accepted: June 11, 2020; Published online: June 17, 2020 How to cite this article: Vučić T, Ivanović A, Nikolić S, Jovanović J, Cvijanović M. Reproductive characteristics of two Triturus species (Amphibia: Caudata). Arch Biol Sci. 2020;72(3):321-8.